The Impact of 68Gallium DOTA PET/CT in Managing Patients With Sporadic and Familial Pancreatic Neuroendocrine Tumours - Cuthbertson, Daniel J.; Barriuso, Jorge; Lamarca, Angela; Manoharan, Prakash; Westwood, Thomas; Jaffa, Matthew; Fenwick, Stephen W.; Nuttall, Christina; Lalloo, Fiona; Prachalias, Andreas; Pizanias, Michail; Wieshmann, Hulya; et al. (Frontiers in Endocrinology, 2021)
Objective Pancreatic neuroendocrine tumours (panNETs) arise sporadically or as part of a genetic predisposition syndrome. CT/MRI, endoscopic ultrasonography and functional imaging using Octreoscan localise and stage disease. This study aimed to evaluate the complementary role of 68Gallium (68Ga)-DOTA PET/CT in managing patients with panNETs. Design A retrospective study conducted across three tertiary UK NET referral centres. Methods Demographic, clinical, biochemical, cross-sectional and functional imaging data were collected from patients who had undergone a 68Ga-DOTA PET/CT scan for a suspected panNET. Results We collected data for 183 patients (97 male): median (SD) age 63 (14.9) years, 89.1 vs. 9.3% (n=163 vs. 17) alive vs. dead (3 data missing), 141 sporadic vs. 42 familial (MEN1, n=36; 85.7%) panNETs. Non-functional vs. functional tumours comprised 73.2 vs. 21.3% (n=134 vs. 39) (10 missing). Histological confirmation was available in 89% of individuals (n=163) but tumour grading (Ki67 classiifcation) was technically possible only in a smaller cohort (n=143): grade 1, 50.3% (n=72); grade 2, 46.2% (n=66) and grade 3, 3.5% (n=5) (40 histopathological classification either not technically feasible or biopsy not perfomed). 60.1% (n=110) were localised, 14.2% (n=26) locally advanced and 23.5% (n=43) metastatic (4 missing). 224 68Ga-DOTA PET/CT scans were performed in total for: diagnosis/staging 40% (n=88), post-operative assessment/clinical surveillance 53% (n=117) and consideration of peptide receptor radionuclide therapy (PRRT) 8% (n=17) (2 missing). PET/CT results confirmed other imaging findings (53%), identified new disease sites (28.5%) and excluded suspected disease (5%). Overall, 68Ga-DOTA PET/CT imaging findings provided additional information in 119 (54%) patients and influenced management in 85 (39%) cases. Conclusion 68Ga-DOTA PET/CT imaging more accurately stages and guides treatment in patients with sporadic/familial panNETs with newly diagnosed/recurrent disease.